Challenges of Using E-learning in Medical Education Based on Medical Students’ Opinion - Alqahtani, Refaa Hussein (Journal of Curriculum and Teaching Methodology, 2023)
The aim of this study was to identify the challenges of using e learning in medical education based on medical student’s opinion. The descriptive approach was used to answer the research questions, questionnaire of 43 items was developed and distributed to 312 students of medicine collage at King Saud university. The results of the study showed that there was administrative and organizational challenges, the main challenges were the shortage of an e-learning strategy in the college and the lack of students training for using programs, difficulty of using these technologies in some courses, inability to use the available facilities in optimal way, the lack of specialists who can design an electronic courses and the high cost of the high speed Internet that cannot be afford by the student and their parents. In addition to that the study found there were technical difficulties such as the weakness of the network, the lack of sufficient technical support, as well as there were technical problems related to the Blackboard e-learning system. Based on these findings, It has been recommended to develop an appropriate strategy for e-learning in the college. Moreover, it has been advised to take the advantage from the available experts in educational technology to design appropriate programs to activate e-learning in practical and clinical applications. Finally, arrange for training courses and workshops to train the faculty members to carry out e-learning effectively.